2015
DOI: 10.5770/cgj.18.158
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Feasible Physical Activity Programs for Long-Term Care Homes in the Ontario Context

Abstract: BackgroundStructured exercise programs for frail institutionalized seniors have shown improvement in physical, functional, and psychological health of this population. However, the 'feasibility' of implementation of such programs in real settings is seldom discussed. The purpose of this systematic review was to gauge feasibility of exercise and falls prevention programs from the perspective of long-term care homes in Ontario, given the recent changes in funding for publically funded physiotherapy services. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 61 publications
0
8
0
1
Order By: Relevance
“…This is relevant because persons living in LTCFs have poor physical fitness and high physical dependence, which could be associated to poor mental health. 7,27 While the neurobiological mechanisms underlying physical fitness and cognitive function have not been fully elucidated, a number of studies have shown that persons who are more physically active exhibit better mental health. 24,28 Many neurobiological processes related to physical fitness, such as improved cerebral blood flow, increased trophic factors, neurotransmitter synthesis, and synaptic branch enhancement, could be associated with brain integrity.…”
Section: Discussionmentioning
confidence: 99%
“…This is relevant because persons living in LTCFs have poor physical fitness and high physical dependence, which could be associated to poor mental health. 7,27 While the neurobiological mechanisms underlying physical fitness and cognitive function have not been fully elucidated, a number of studies have shown that persons who are more physically active exhibit better mental health. 24,28 Many neurobiological processes related to physical fitness, such as improved cerebral blood flow, increased trophic factors, neurotransmitter synthesis, and synaptic branch enhancement, could be associated with brain integrity.…”
Section: Discussionmentioning
confidence: 99%
“… 54 , 55 Supervision by exercise specialists or by trained physiotherapists would be preferable, but will generally involve additional charge for the institution. A review by Shakeel et al, 56 suggest that effective group-based exercise programs can be implemented in nursing homes with trained staff members (nurses or volunteers).…”
Section: Discussionmentioning
confidence: 99%
“…One extensive systematic review found that effective group-based exercise programs can be implemented in LTC hospitals with monetary resource constraints, with the use of trained staff members (e.g. nurses, PSWs, and volunteers), using simple and inexpensive equipment, and carried out three times per week for 30–45 minutes per session 68. More research should determine how to optimize the feasibility of exercise programs specifically targeted to the elderly population residing in different long-term settings and/or their homes, and a patient inclusion/exclusion guideline should be created.…”
Section: Discussionmentioning
confidence: 99%